A cross-cultural clinical comparison between subjects with obsessive-compulsive disorder from the United States and Brazil. (August 2017) - Medeiros, Gustavo C.; Torres, Albina R.; Boisseau, Christina L.; Leppink, Eric W.; Eisen, Jane L.; Fontenelle, Leonardo F.; do Rosário, Maria C.; Mancebo, Maria C.; Rasmussen, Steven A.; Ferrão, Ygor A.; Grant, Jon E.
Abstract: Although OCD is a global problem, the literature comparing, in a direct and standardized way, the manifestations across countries is scarce. Therefore, questions remain as to whether some important clinical findings are replicable worldwide, especially in the developing world. The objective of this study was to perform a clinical comparison of OCD patients recruited in the United States (U.S.) and Brazil. Our sample consisted of 1187 adult, treatment-seeking OCD outpatients from the U.S. ( n =236) and Brazil ( n =951). With regards to the demographics, U.S. participants with OCD were older, more likely to identify as Caucasian, had achieved a higher educational level, and were less likely to be partnered when compared to Brazilians. Concerning the clinical variables, after controlling for demographics the two samples presented largely similar profiles. Brazilian participants with OCD, however, endorsed significantly greater rates of generalized anxiety disorder and post-traumatic stress disorder, whereas U.S. subjects were significantly more likely to endorse a lifetime history of addiction (alcohol-use and substance-use disorders). This is the largest direct cross-cultural comparison to date in the OCD field. Our results provide much needed insight regarding the development of culture-sensitive treatments. Highlights: Largest direct cross-cultural comparison to date in the obsessive-compulsive disorder field. Very similar profile in terms of age of onset of OCD symptoms and severity. There are relevant differences in educational level and co-occurring psychiatric disorders. Our results provide much needed insight regarding the development of culture-sensitive care. Collaborations such as this analysis create opportunities for large cross-cultural studies.